2008
DOI: 10.1128/jvi.01510-08
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Evasion Paradox: Immunoevasins of Murine Cytomegalovirus Enhance Priming of CD8 T Cells by Preventing Negative Feedback Regulation

Abstract: Cytomegaloviruses express glycoproteins that interfere with antigen presentation to CD8 T cells. Although the molecular modes of action of these "immunoevasins" differ between cytomegalovirus species, the convergent biological outcome is an inhibition of the recognition of infected cells. In murine cytomegalovirus, m152/gp40 retains peptide-loaded major histocompatibility complex class I molecules in a cis-Golgi compartment, m06/gp48 mediates their vesicular sorting for lysosomal degradation, and m04/gp34, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
80
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 70 publications
8
80
0
Order By: Relevance
“…3B) is in line with this hypothesis. CD8 depletion experiments performed by Böhm et al (84) did not substantially reduce viral gene expression in draining LNs of MCMV-infected mice, indicating that the bulk of the viral Ag is produced in other cell types of secondary lymphoid organs, which is in agreement with our data. It might be worth reexamining the MCMV-infected cell types in LNs and spleen using histochemical techniques to learn which cells provide the viral Ag for priming of CD8 + T cells.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…3B) is in line with this hypothesis. CD8 depletion experiments performed by Böhm et al (84) did not substantially reduce viral gene expression in draining LNs of MCMV-infected mice, indicating that the bulk of the viral Ag is produced in other cell types of secondary lymphoid organs, which is in agreement with our data. It might be worth reexamining the MCMV-infected cell types in LNs and spleen using histochemical techniques to learn which cells provide the viral Ag for priming of CD8 + T cells.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, the CD8a 2 DCs may be rather important for stimulating CD4 + T cell help and play a minor role in priming of the CD8 + T cell response (4,5). Second, Böhm et al (84) reported that CD8 + T cell priming is less efficient after infection with DvRAP mutants and explained this with a negative feedback reaction of newly primed CD8 + T cells, leading to the rapid elimination of infected cells in the LN, limiting further supply of viral Ags. The somewhat smaller T cell response that we observed after infection with the DvRAP mutants can be explained by this "immune evasion paradox" described by Bö hm et al (84).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Fig. 2A by the time course of viral replication in the recipients' lungs, mutant virus replicated like WT virus only in the first 2 weeks, which is consistent with unaltered replicative fitness in the absence of immune cells (4). In contrast, significantly more-efficient control of the .…”
mentioning
confidence: 67%
“…In the MCMV model, evasins interfere with antiviral protection through certain virus-specific T cells (62,63) and enhance viral latency (64), in the face of a paradoxically increased T cell response that is likely due to more efficient cross-presentation of viral Ag (65). In a rhesus macaque model, deletion of US2-11 does not alter the course of primary CMV infection but prevents superinfection of CMV-positive animals (66).…”
Section: Discussionmentioning
confidence: 99%